The National SOM Survey 2002 - SOM Institute, University of Gothenburg (University of Gothenburg, 2004)
Since 1986 the SOM-institute has been carrying out an annual nation-wide survey of Swedish opinions. This is accordingly the seventeenth survey in this series. The SOM-institute is a collaboration between three departments at Göteborg University: the Institute for Journalism and Mass Communication, the Department of Political Science, and the School of Public Administration. Since 1998 the survey includes two nation representative samples and uses two different mail questionnaires. One of the questionnaires mainly deals with questions on politics, economy and working life, while the other mainly deals with media, culture and health. One third of the questions asked in the two questionnaires are common for both samples, for example questions about media habits, political attitudes, leisure activities, and social background.

Both questionnaires in National SOM 2002 include nine different subject fields. A large number of the questions are common for both questionnaires, hence they can be studied with double sample size. Both questionnaires include the subject fields: politics and society; possession of technical equipment and the internet; and background questions. The questionnaire on politics also include: mass media; Sweden's relationship to the surrounding world; energy, nuclear power and the future; work and industry; leisure time, interests and health; and democracy and influence. The media questionnaire include: news and papers; mass media and society; the EU summit meeting in Göteborg; libraries; leisure time; and 'Your yesterday'.

Purpose:

The main purpose is to establish time series that enable researchers to analyse how various changes in society affect people's attitudes and behaviour.

Detta är den sjuttonde undersökningen i serien Riks-SOM, en nationell frågeundersökning med syfte att kartlägga den svenska allmänhetens vanor och attityder på temat samhälle, opinioner och medier.

Riks-SOM 2002 genomfördes som två undersökningar med två representativa urval och två olika formulär, där datainsamlingarna genomfördes parallellt och under identiska förhållanden. Frågeformulären skiljer sig något åt i det att tyngdpunkten i det ena formuläret ligger på politik och samhälle, medan det andra har en tonvikt på frågor om medier, kultur och livsstil. Ett stort antal frågor är gemensamma för båda frågeformulären och kan därmed bearbetas med dubbel urvalsstorlek.

Båda formulären innehåller nio olika frågeområden. Gemensamma frågeområden är: politik och samhälle; teknikinnehav och internet; samt bakgrund. Politikformuläret innehåller även: massmedier; Sveriges förhållande till omvärlden; energi, kärnkraft, miljö och framtid; arbete och industri; fritid, intresse och hälsa; samt demokrati och inflytande. Medieformuläret tar även upp: nyheter och tidningar; massmedier och samhälle; EU:s toppmöte i Göteborg; bibliotek; fritid; samt 'Din gårdag'.

Syfte:

Huvudsyftet är att etablera tidsserier som gör det möjligt att analysera hur olika samhällsförändringar påverkar människors attityder och beteenden.
Den nationella SOM-undersökningen 2002
Riks-SOM 2002
Keywords: mass media; massmedia; population migration; migration; energy; energi; environment; miljö; health; hälsa; european union; europeiska unionen; local government services; kommunal service; nuclear energy; kärnkraft; political participation; politiskt deltagande; television viewing; tv-tittande; internal politics; inrikespolitik; mass media use; mediaanvändning; renewable energy; förnybar energi; radio listening; radiolyssnande; CORS; CORS; Media; Media; Energy and natural resources; Energi och naturresurser; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap